Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Okay, the f^-1 means we need to invert the original function. So switch x's and y's and solve for y.
y = 3x - 27/14
x = 3y - 27/14
-3y = -x - 27/14
y = 1/3x + 9/14
Then plug in 241
y = 80 1/3 + 9/14
y = 80 41/42
Now you have to plug it back into the original function.
So:
y = 3(80 41/42) - 27/14
y = 3401/42 - 27/14
y = 79.0476190476 or 79 and 1/21
y = 3x - 27/14
x = 3y - 27/14
-3y = -x - 27/14
y = 1/3x + 9/14
Then plug in 241
y = 80 1/3 + 9/14
y = 80 41/42
Now you have to plug it back into the original function.
So:
y = 3(80 41/42) - 27/14
y = 3401/42 - 27/14
y = 79.0476190476 or 79 and 1/21
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.